Depleting hepatitis B virus relaxed circular DNA is necessary for resolution of infection by CRISPR-Cas9 - Dmitry Kostyushev; Anastasiya Kostyusheva; Sergey Brezgin; Natalia Ponomareva; Natalia F. Zakirova; Aleksandra Egorshina; Dmitry V. Yanvarev; Ekaterina Bayurova; Anna Sudina; Irina Goptar; Anastasiya Nikiforova; Elena Dunaeva; et al. (Elsevier, 2023)
CRISPR-Cas9 systems can directly target the hepatitis B virus (HBV) major genomic form, covalently closed circular DNA (cccDNA), for decay and demonstrate remarkable anti-HBV activity. Here, we demonstrate that CRISPR-Cas9-mediated inactivation of HBV cccDNA, frequently regarded as the "holy grail" of viral persistence, is not sufficient for curing infection. Instead, HBV replication rapidly rebounds because of de novo formation of HBV cccDNA from its precursor, HBV relaxed circular DNA (rcDNA). However, depleting HBV rcDNA before CRISPR-Cas9 ribonucleoprotein (RNP) delivery prevents viral rebound and promotes resolution of HBV infection. These findings provide the groundwork for developing approaches for a virological cure of HBV infection by a single dose of short-lived CRISPR-Cas9 RNPs. Blocking cccDNA replenishment and re-establishment from rcDNA conversion is critical for completely clearing the virus from infected cells by site-specific nucleases. The latter can be achieved by widely used reverse transcriptase inhibitors.